Exergoenvironmental and exergoeconomic analyses of a vertical type ground source heat pump integrated wall cooling system - Akbulut, Ugur; Utlu, Zafer; Kincay, Olcay (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
In this study, exergoenvironmental, and exergoeconomic analyses of wall cooling systems fed by a vertical type of ground source heat pump integrated wall cooling system for cooling were examined experimentally and theoretically in Yildiz Renewable Energy House at Davutpasa Campus of Yildiz Technical University. The examination includes energy, exergy, exergoenvironmental and exergoeconomic analyses, between the dates of 1 July and 30 September 2013. The main aim of this objective is to minimize energy usage in Residential Sector as low as possible. Therefore, a particular system working with low temperature regime was chosen. According to the outcomes; energy and exergy efficiency of all the system have been found as 74.85% and 29.90%. Part-based environmental factor values are calculated. The compressor and underground heat exchanger have the highest values calculated as 0.040 mPts/s, 0.026 mPts/s respectively. The exergoenvironmental impact values of all system are detected as 42.60%. On the other hand; the exergoeconomic factor values of all system are calculated as 77.68%. The value of exergoeconomic factor changes depending on some particular components: accumulator tank, undersoil heat exchanger, evaporator and condenser calculated respectively as 69.43%, 62.59%, 62.53% and 29.15%. As a result; it is found that in order to determine economic and environmental impacts of irreversibilities occurring in the system and its components, economic and environmental analyses of thermal system as well as wall cooling systems, should be done based on exergy concept. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Cooling; Energy; Exergy; Heat pump; Exergoenvironmental; Exergoeconomic; Wall cooling; EXERGY ANALYSIS; UNCERTAINTY; PERFORMANCE; IMPACT; FLOOR; ROOM; Thermodynamics; Energy & Fuels; Engineering; Mechanics